Dickeya dadantii, a plant pathogenic bacterium producing Cyt-like entomotoxins, causes septicemia in the pea aphid Acyrthosiphon pisum. - Denis Costechareyre (Public Library of Science (PLoS), 2012)
Dickeya dadantii (syn. Erwinia chrysanthemi) is a plant pathogenic bacteria that harbours a cluster of four horizontally-transferred, insect-specific toxin genes. It was recently shown to be capable of causing an acute infection in the pea aphid Acyrthosiphon pisum (Insecta: Hemiptera). The infection route of the pathogen, and the role and in vivo expression pattern of these toxins, remain unknown. Using bacterial numeration and immunolocalization, we investigated the kinetics and the pattern of infection of this phytopathogenic bacterium within its insect host. We compared infection by the wild-type strain and by the Cyt toxin-deficient mutant. D. dadantii was found to form dense clusters in many luminal parts of the aphid intestinal tract, including the stomach, from which it invaded internal tissues as early as day 1 post-infection. Septicemia occurred soon after, with the fat body being the main infected tissue, together with numerous early infections of the embryonic chains showing embryonic gut and fat body as the target organs. Generalized septicemia led to insect death when the bacterial load reached about 10(8) cfu. Some individual aphids regularly escaped infection, indicating an effective partial immune response to this bacteria. Cyt-defective mutants killed insects more slowly but were capable of localisation in any type of tissue. Cyt toxin expression appeared to be restricted to the digestive tract where it probably assisted in crossing over the first cell barrier and, thus, accelerating bacterial diffusion into the aphid haemocel. Finally, the presence of bacteria on the surface of leaves hosting infected aphids indicated that the insects could be vectors of the bacteria.